An aggressive tumor in parotid gland - Dr. Sathish Selvakumar; Dr. Rajalakshmi Vaithyanathan (Tropical Journal of Pathology and Microbiology, 2017)
Non Hodgkin Lymphoma (NHL) of salivary gland (SG) is rare with an incidence of 2-5%. We describe a stage III, high grade NHL of parotid gland in a background of benign lymphoepithelial lesions. A 54 year female presented with a right side facial mass since 6 months. Fine needle aspiration cytology (FNAC) suggested a lymphoproliferative disorder and superficial parotidectomy was done. Histopathology and immunohistochemistry (IHC) revealed an extranodal marginal zone NHL with transformation to high grade diffuse large B cell lymphoma. SG lymphoma should be considered in elderly and IHC helps in prognostication and treatment protocols.